Enhanced Removal of Pb(II) from Aqueous Solution using EDTA‐Modified Magnetic Graphene Oxide. Issue 4 (9th February 2021) - Xing, Cuijuan; Xia, Aiqing; Yu, Ling; Dong, Lili; Hao, Yongchao; Qi, Xingcun
Abstract: Ethylenediaminetetraacetic acid (EDTA) groups are successfully linked to magnetic graphene oxide (MGO) by a silanization reaction between N ‐(trimethoxysilylpropyl) ethylenediaminetriacetic acid and OH on the surface of MGO. The EDTA‐modification enhances the adsorption capacity of MGO because of the chelating ability of EDTA. The adsorption behavior of Pb(II) and the effects of solution conditions such as contact time, initial Pb(II) concentration, and pH (1–9) are investigated. The adsorption capacity for Pb(II) removal is found to be 211.3 mg g −1 and the adsorption process is completed at pH 6.8 within 50 min. The process is shown to follow a pseudo‐second‐order kinetic rate. The isothermal data reveal that the adsorption process of Pb(II) is well‐matched with the Freundlich model. In addition, the magnetic composite can be effectively and simply separated by an external magnetic field. Therefore, MGO‐EDTA can potentially serve as an adsorbent for the separation and removal of Pb(II) from water. Abstract : Improvement of the decontamination efficiency for potentially toxic metals through eco‐friendly adsorption techniques is an important issue. The adsorption behaviors of Pb(II) on MGO‐EDTA are investigated. This research demonstrates that MGO‐EDTA can potentially serve as an adsorbent for the removal of Pb(II) from water.